The International Trauma Questionnaire: development of a self‐report measure of ICD‐11 PTSD and complex PTSD. (3rd September 2018) - Cloitre, M.; Shevlin, M.; Brewin, C. R.; Bisson, J. I.; Roberts, N. P.; Maercker, A.; Karatzias, T.; Hyland, P.
Abstract : Objective: The purpose of this study was to finalize the development of the International Trauma Questionnaire (ITQ), a self‐report diagnostic measure of post‐traumatic stress disorder (PTSD) and complex PTSD (CPTSD), as defined in the 11th version of the International Classification of Diseases (ICD‐11). Method: The optimal symptom indicators of PTSD and CPTSD were identified by applying item response theory (IRT) analysis to data from a trauma‐exposed community sample ( n = 1051) and a trauma‐exposed clinical sample ( n = 247) from the United Kingdom. The validity of the optimized 12‐item ITQ was assessed with confirmatory factor analyses. Diagnostic rates were estimated and compared to previous validation studies. Results: The latent structure of the 12‐item, optimized ITQ was consistent with prior findings, and diagnostic rates of PTSD and CPTSD were in line with previous estimates. Conclusion: The ITQ is a brief, simply worded measure of the core features of PTSD and CPTSD. It is consistent with the organizing principles of the ICD‐11 to maximize clinical utility and international applicability through a focus on a limited but central set of symptoms. The measure is freely available and can be found in the body of this paper.